Assessment of Track Quality in Trial Test Sections by Spot and Continuous Method - Smalo, Michal; Izvolt, Libor (Communications - Scientific letters of the University of Zilina, 2015)
The quality of track alignment and track geometry is an essential precondition of safe and economical operation of railway track. The paper provides an analysis of diagnostics of relative track geometry parameters and evaluation of measurement deviations carried out by the spot and continuous method in sections of the ballasted track, transition areas and sections with the slab track structure.